Evaluation of the efficacy of a new low-level laser therapy home protocol in the treatment of temporomandibular joint disorder-related pain: A randomized, double-blind, placebo-controlled clinical trial. Issue 2 (4th March 2021) - Del Vecchio, Alessandro; Floravanti, Miriam; Boccassini, Armando; Gaimari, Gianfranco; Vestri, Annarita; Di Paolo, Carlo; Romeo, Umberto
ABSTRACT: Objective : This study analyzed a home, low-level laser therapy (LLLT) protocol to manage temporomandibular joint disorders (TMJDs)-related pain. Methods : Ninety TMJD patients (12M, 78F) between 18 and 73 years were randomly subdivided into three groups. Study group (SG) received 1-week home protocol LLLT by B-cure Dental Pro: 808 nm, 5 J/min, 250 mW, 15 KHz for 8', 40 J each, over pain area, twice daily. Placebo group (PG) followed the same protocol using sham devices. Drugs group (DG) received conventional drugs. Pain was evaluated by visual analog scale (VAS) before and after therapy. Results : Statistical analysis showed that treatment was effective (F(2, 83) = 4.882; p = .010). Bonferroni post-hoc analysis indicated a lower pain decrease in PG. SG registered a 34-point decrease per patient, while in PG and DG, the reduction was 25.6 and 35.3, respectively. Conclusion : The study supports the efficacy of home LLLT management of TMJD related pain.